Reconstruction Options in Oral Cavity Cancer Surgery: A Tertiary Care Centre Experience - Saraf, Aditiya; Ahmad, Raies; Dhar, Sanjay; Jamwal, Padam Singh (International Journal of Innovative Research in Medical Science, 2020)
Aims & Objectives: To study various reconstructive options in oral cavity cancer surgeries at our centre. Material and Methods: The present prospective study was conducted in the Department of ENT, GMC Jammu from January 2018 to December 2019 on 20 diagnosed cases of head and neck malignancy, who underwent reconstruction options such as local flap, pedicled flap or free flap. Results: Out of 11 lip cancer patients, 1 had local flap repair, rest all underwent primary closure. Out of 7 tongue carcinoma patients, 2 underwent free flap repair while 5 had primary closure. Out of 2 buccal carcinoma patients, one underwent excision with split thickness skin graft repair and 1 had pedicled flap repair. All reconstructions were having successful functional outcome at 6 months after surgery. Conclusion: From our study we can conclude that if performed with utmost care, the functional outcomes of various modes of reconstruction in oral cavity cancer surgeries from simple primary closure to complex ones like pedicled or free flaps, can be satisfactory.